Os sem-lugar: uma análise de trajetórias de jovens que vivem nas ruas de Porto Alegre - Estivalet, Anelise Gregis (2008)
The main issue approached in this dissertation concerns the daily lives of young people that live on the streets in Porto Alegre. I have used the expression placeless to point out what their reports have shown, i.e. it seems that they were born without a place to stay in this world; when they were born, they did not have a place either in their families or in their original communities. Today, as adults, they try to find their place. I have become interested in understanding how they went to the streets, the previous and current relationships they have had with their families, as well as the reasons that have led them to either stay or not in these life conditions. The field research has consisted of observations of those young people s routines on the streets and interviews. Analyses of documents and reconstruction of life trajectories have been carried out by means of interviews. These consisted of semi-structured questionnaires presenting short, incomplete sentences. I asked the participants to complete them with the first idea that came to their mind. The research was carried out with four subjects aged 17-20 years old that either live or lived in abandonment situation in big cities. I have also used other instruments, such as photographs and field notes. My hypothesis was that those young subjects, even though walking uneven, hard paths in their lives, have been able to build new forms of relating to the world, other than abandonment and violence, a fact that has been proven to be possible. I have detected that those young people have to face two limitations: time (vital moratorium) and space (urban circuits).